2020
DOI: 10.3389/fncel.2020.00281
|View full text |Cite
|
Sign up to set email alerts
|

Synaptic Organizers in Alzheimer’s Disease: A Classification Based on Amyloid-β Sensitivity

Abstract: Synaptic pathology is one of the major hallmarks observed from the early stage of Alzheimer’s disease (AD), leading to cognitive and memory impairment characteristic of AD patients. Synaptic connectivity and specificity are regulated by multiple trans-bindings between pre- and post-synaptic organizers, the complex of which exerts synaptogenic activity. Neurexins (NRXs) and Leukocyte common antigen-related receptor protein tyrosine phosphatases (LAR-RPTPs) are the major presynaptic organizers promoting synaptog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 169 publications
(268 reference statements)
2
11
0
Order By: Relevance
“…We found that axonal expression of either SorCS1b or SorCS1bΔVPS10 did not significantly affect Slitrk2-induced VGLUT1 accumulation regardless of AβO treatment (Fig 4E and F). This finding is in line with the results of our previous study showing that RPTP-mediated presynaptic differentiation is insensitive to AβOs (Naito et al, 2017;Lee et al, 2020) and suggests that it is also insensitive to SorCS1, consistent with our binding results showing that SorCS1-Fc does not interact with any RPTPs or Slitrks (Fig 1A). In conclusion, these findings suggest that axonal SorCS1b expression rescues AβO-induced impairment of NRXmediated presynaptic organization through cis-interaction with β-NRXs.…”
Section: Sorcs1b Expression In Axons Rescues Aβo-induced Impairment O...supporting
confidence: 93%
“…We found that axonal expression of either SorCS1b or SorCS1bΔVPS10 did not significantly affect Slitrk2-induced VGLUT1 accumulation regardless of AβO treatment (Fig 4E and F). This finding is in line with the results of our previous study showing that RPTP-mediated presynaptic differentiation is insensitive to AβOs (Naito et al, 2017;Lee et al, 2020) and suggests that it is also insensitive to SorCS1, consistent with our binding results showing that SorCS1-Fc does not interact with any RPTPs or Slitrks (Fig 1A). In conclusion, these findings suggest that axonal SorCS1b expression rescues AβO-induced impairment of NRXmediated presynaptic organization through cis-interaction with β-NRXs.…”
Section: Sorcs1b Expression In Axons Rescues Aβo-induced Impairment O...supporting
confidence: 93%
“…We found that axonal expression of either SorCS1b or SorCS1bΔVPS10 did not significantly affect Slitrk2-induced VGLUT1 accumulation regardless of AβO treatment (Fig 4E and F). This finding is in line with the results of our previous study showing that RPTP-mediated presynaptic differentiation is insensitive to AβOs (Lee et al, 2020;Naito et al, 2017) and suggests that it is also insensitive to SorCS1, consistent with our binding results showing that SorCS1-Fc does not interact with any RPTPs or Slitrks (Fig 1A). In conclusion, these findings suggest that axonal SorCS1 expression rescues AβO-induced impairment of NRX-mediated presynaptic organization through cis-interaction with β-NRXs.…”
Section: Sorcs1 Expression In Axons Rescues Aβo-induced Impairment Of...supporting
confidence: 93%
“…Fluctuations in NRXN1 levels and other neurexins are implicated in disrupting the balance of excitatory and inhibitory signals at synapses, resulting in damage and cognitive impairment seen early in AD [ 40 ]. NRXN1 has been found to interact with the Aβ plaques in AD leading to synaptic transmission impairment [ 41 ]. Presenilins, proteases involved in Aβ formation, proteolytically process neurexins, and the dysfunction of this pathway may be associated with AD [ 42 ].…”
Section: Discussionmentioning
confidence: 99%